Effects of various Agrobacterium rhizogenes strains on hairy root induction and analyses of primary and secondary metabolites in Ocimum basilicum - Sathasivam, Ramaraj; Choi, Minsol; Radhakrishnan, Ramalingam; Kwon, Haejin; Yoon, Jiwon; Yang, So Hwi; Kim, Jae Kwang; Chung, Yong Suk; Park, Sang Un (Frontiers in Plant Science, 2022)
The hairy root (HR) culture system is an excellent alternative strategy to the whole plant system for producing valuable compounds. However, selection of suitable Agrobacterium strain for the successful induction of HR is an essential step for enhanced production of beneficial secondary metabolites. In this study, we examined the transformation efficiency of various A. rhizogenes strains (ATCC 13333, ATCC 15834, A4, R1000, R1200, and R1601) for transgenic HRs induction in Ocimum basilicum. Among the tested strains, the R1601 was found to be one of the most promising strain for mass production of HR in terms of transformation efficiency (94%) and the number and length of HR (8.4 ± 0.52 and 1.68 ± 0.14 cm). The HR induced by the same strain exhibited highest levels of rosmarinic acid level (62.05±4.94 µg/g DW) and total phenolic content (62.3±4.95 µg/g DW). A total of 55 metabolites were identified using high-performance liquid chromatography (HPLC) and gas chromatography–time-of-flight mass spectrometry (GC-TOFMS). The PCA and PLS-DA plot of the identified metabolites showed that HR induced by A4 and ATCC 15834 displayed variation in primary and secondary metabolite contents. Analysis of the metabolic pathway identified a total of 56 pathways, among which 35 were found to be impacted. A heat map and hierarchical clustering analysis indicated that HR induced by different Agrobacterium strains exhibited differential metabolites profiles. In conclusion, Agrobacterium strains R1601 is one of the best and most promising strains for inducing mass HR production and enhanced levels of secondary metabolites in O. basilicum.